Desvulcanização termomecânica contínua de borracha natural da banda de rodagem de pneus automotivos por meio do processo de extrusão em rosca dupla - Nunes, Anderson Thadeu (Universidade Federal de São Carlos, 2015)
The Natural rubber is a renewable source material widely used in the manufacture of automotive tire tread. The vulcanization results in a high thermodynamic stability and wide working range materials. However, after the end of life serious environmental and public health problems can occur because of improper disposal or burning. Recycling (devulcanization) is an attractive alternative because it takes advantage of the invested energy potential and relieves the pressures for planting new areas. The devulcanization of natural rubber automotive tire tread was performed by means of double screw extrusion process and intermeshing co-rotating. The directionality and magnitude of shear stress achieved in the process are able to overcome the energy of chemical bonds that make up the cross- linking of vulcanized NR. The devulcanization configures the convertion of three-dimensional structure in two-dimensional for selective splitting of crosslinking preserving such bonds between carbons of the Natural Rubber macromolecular chain. Virgin Natural Rubber compounds and post-consumer load tire tread underwent vulcanization process after being cryogenically milled. The devulcanization was carried out by assessing the influence of the extrusion process parameters, the effect of the particle size range, the presence of thermoplastic material and the addition of antioxidant. After extrusion, it was evaluated the magnitude of the soluble fraction of the extrudates. Soluble were evaluated for thermal stability, thermal behavior and the chemical groups present. They were obtained soluble content exceeding 50%. The most significant were obtained for compound of NR extruded without thermoplastic material. Thermal and chemical analysis indicated the presence of natural rubber molecules. Composite rubber virgin Natural and Natural Rubber devulcanized were prepared and vulcanized. The mechanical properties of tensile strength and hardness of these composites were comparable to those of virgin material, showing that the co-rotation and interpenetrating twin screw extrusion process has great potential for devulcanization for Natural Rubber.
Recycling of natural rubber of automotive tire tread by twin screw extruder
Keywords: Polímeros; Reciclagem; Processos de extrusão; Borracha natural; Desvulcanização; ENGENHARIAS